Kolonialität und Geschlecht im 20. Jahrhundert Eine Geschichte der weißen Schweiz - Purtschert, Patricia (Postcolonial Studies, 2019)
National identity and patriarchal gender roles - in what ways are both intertwined with »colonization«? An examination that takes Switzerland as an example.